Pengaruh Tindakan Bullying terhadap Kesehatann Mental pada Siswa SMP Katolik Pineleng, Kabupaten Minahasa - Ria Angelina Jessica Rotinsulu; Sri Atikah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Bullying is an action carried out by individuals or groups who feel stronger to hurt weaker victims, whether physically, verbally or emotionally, repeatedly without any resistance, with the aim of making the victim suffer. The research aims to determine the effect of bullying on the mental health of adolescents at St. Catholic Middle School. Fransiskus Xaverius Pineleng, as well as understanding the extent to which bullying impacts the psychological condition of students in the school environment. This type of research is quantitative using a cross sectional approach. The research was conducted at St. Catholic Middle School. Fransiskus Xaverius Pineleng in August 2024. The population in this study was all 47 junior high school students in grades 7, 8 and 9. Non probability sampling was taken using a purposive sampling approach of 30 respondents. The instruments used were the Olweus Bully/Victim Questionnaire-Revised and Self Questionnaire (SRQ). The dependent variable is bullying which has 30 questions and the independent variable is mental health which has 20 questions. The results showed that in the low bullying category, 20% of students experienced mental health problems and 26.7% were not disturbed. Meanwhile, in the high bullying category, 26.7% of students experienced mental health problems and another 26.7% were not disturbed. The chi square test produces a p-value of 0.980, which indicates there is no significant effect (p > 0.05).